Combating terrorism and the use of force against a state: a relook at the contemporary world order - Hamid, Abdul Ghafur@Khin Maung Sein (Yijun Institute of International Law, 2015)
Self-defence has long been understood as an inherent right of a State when it is militarily attacked by another State. After September 11, however, there have been attempts to reinterpret the meaning of ‘armed attack’ under Article 51 of the UN Charter to include attacks by terrorists - non-State actors. This paper critically examines the legal and policy considerations that promote a right of self-defence against terrorists by means of thoroughly analyzing the text of the UN Charter, State practice and the jurisprudence of the ICJ. The paper finds that a terrorist attack as such may not be an armed attack within the meaning of Article 51 of the Charter unless it is an act of a State or directly imputable to a State and is on a large scale with substantial effects. The paper concludes that unilateral use of force against a State in the name of self-defence is not the correct way of combating terrorism and that there are effective alternatives such as addressing the root causes of terrorism, resorting to law enforcement mechanisms or coercive countermeasures, and strengthening multilateralism.